The ecological thought - Morton, Timothy, 1968- (Harvard University Press, 2010)
"The author argues that all forms of life are interconnected and that no being, construct, or object can exist independently from the ecological entanglement, nor does "nature" exist as an entity separate from the uglier or more synthetic elements of life. Realizing this interconnectedness is what the author calls the ecological thought. He investigates the philosophical, political, and aesthetic implications of this interconnectedness."--Provided by publisher.